2014
DOI: 10.1111/jph.12280
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Pathogenicity of Fusarium oxysporum f.sp. melonis Races from Different Areas of Italy

Abstract: Fusarium wilt caused by Fusarium oxysporum f.sp. melonis (FOM) is a devastating disease of melon worldwide. Pathogenicity tests performed with F. oxysporum isolates obtained from Italian melon‐growing areas allowed to identify thirty‐four FOM isolates and the presence of all four races. The aims of this work were to examine genetic relatedness among FOM isolates by race determination and to perform phylogenetic analyses of identified FOM races including also other formae speciales of F. oxysporum of cucurbits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In addition, a new recessive gene fom-4 , linked to Fom-1 , confers resistance to races 0, 2 in the Tortuga melon line (Oumouloud et al, 2010 ). Despite these sources of resistance, fusarium wilt remains a relevant disease mainly because of FOM race 1.2 (FOM1.2) that represents the most widespread and harmful race causing economic losses up to 100% of melon yield (Luongo et al, 2015 ). Resistance to race 1.2 is complex being controlled by multiple recessive genes and strongly affected by the environment (Perchepied and Pitrat, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new recessive gene fom-4 , linked to Fom-1 , confers resistance to races 0, 2 in the Tortuga melon line (Oumouloud et al, 2010 ). Despite these sources of resistance, fusarium wilt remains a relevant disease mainly because of FOM race 1.2 (FOM1.2) that represents the most widespread and harmful race causing economic losses up to 100% of melon yield (Luongo et al, 2015 ). Resistance to race 1.2 is complex being controlled by multiple recessive genes and strongly affected by the environment (Perchepied and Pitrat, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…27: 66. 1940, Cai et al 2003Thatcher et al 2012, Baysal et al 2013, Bennett et al 2013, Covey et al 2014, Gawehns et al 2014, Mirtalebi & Banihashemi 2014, Bertoldo et al 2015, Hansen et al 2015, Nirmaladevi et al 2016, Taylor et al 2016, Bilju et al 2017, Jelinski et al 2017 Katan 1999, Katan & Di 2013, Poli et al 2013, Covey et al 2014, Gawehns Primo 1999, Mirtalebi & et al 2014, Luongo et al 2014, Ma et al 2014…”
Section: Bolley 1901mentioning
confidence: 99%
“…So clearly F. oxysporum is a ubiquitous fungus that is able to adapt to many types of environments, although it is more frequently encountered in the soil where its density is important both in cultivated and noncultivated ecosystems. Focus is generally made on the diversity of pathogenic populations to understand the origins of this particular trait (Baayen et al 2000;Groenewald et al 2006;Luongo et al 2015;O'Donnell et al 1998O'Donnell et al , 2004. However, many studies have revealed an incredible intraspecific diversity within F. oxysporum (Demers et al 2015;Edel et al 2001;Laurence et al 2012;Lori et al 2004).…”
Section: Is F Oxysporum Only a Soilborne Fungus?mentioning
confidence: 99%